THE INFLUENCE OF THE IB MASLAHAH GOLD OWNERSHIP MARKETING STRATEGY ON CUSTOMER INTEREST AT BANK JABAR BANTEN (BJB) KCP SUMEDANG - Nurhasanah Nurhasanah; Resa Fauziah; Asep Ganjar Sukarelawan (Al - Mujaddid: Jurnal Ilmu-ilmu Agama, 2024)
Marketing strategy is the spearhead for banks to introduce their products to attract public interest. Gold is a precious metal that is in great demand by the public because it is one of the alternative long-term investments with minimal risk. The way to get gold can be by buying or by installments. In fact, many people still do not know about gold installment products. Profitable business opportunities in gold investment have made many companies compete to launch gold products, including Islamic banking in Indonesia. Bank BJB KCP Sumedang seeks to offer gold ownership products as one of the investment options that are in accordance with Islamic principles.This study uses quantitative methods using observation, interview, and questionnaire methods to obtain data on the influence of marketing strategies for ib maslahah gold ownership products on customer interest at Bank Jabar Banten (BJB) Syariah KCP Sumedang. This study took a sample of 62 customers (gold ownership products) during January 2024 - June 2024. The results of this study indicate that marketing strategies have a positive and significant effect on customer interest. This is based on the results of the t-test with a sig value <0.05 and based on the results of a simple linear regression analysis which has a positive or unidirectional regression coefficient value so that it can be interpreted that the better the marketing strategy, the more it will increase customer interest.